OPTIMIZATION OF DUCKWEED (LEMNA MINOR) INCLUSION LEVELS TO IMPROVE NUTRITIONAL QUALITY AND PRODUCTION EFFICIENCY OF NILE TILAPIA (OREOCHROMIS NILOTICUS) BY RESPONSE SURFACE MODELLING - Marinus, E.; Oghenevwairhe, E. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The introduction of alternative feeds that increase aquaculture productivity at minimal cost to the environment and the economy plays an increasingly important role in sustainable aquaculture. In this paper, the optimal inclusion level of Lemna minor (duckweed) in the culture of Oreochromis niloticus has been assessed using quadratic response surface modelling. They were experimented over 12 weeks with four feeding regimes; T0 (100% commercial feed), T1 (50% feed + duckweed), T2 (100% feed + duckweed), and T3 (duckweed only). Standard protocols were used to analyse proximate and mineral compositions. Findings showed a nonlinear response pattern, with the highest protein (18.99%) and lipid (6.36%) levels at intermediate inclusion levels. High rates of duckweed addition increased moisture content and reduced nutrient density, consistent with dilution effects reported in the fish feeding literature. There was an optimal performance level of 45-55% inclusion, as shown by a composite Nutritional Efficiency Index (NEI). The results support an eco-nutritional optimization model, indicating that regulated duckweed incorporation improves the efficiency and quality of aquaculture.